2002
DOI: 10.1046/j.1365-2222.2002.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell cytokine responses to outer membrane proteins of Haemophilus influenzae and the house dust mite allergens Der p 1 in allergic and non‐allergic subjects

Abstract: The outer membrane protein antigens of the ubiquitous colonizing bacteria Haemophilus influenzae induce Th1 cytokine responses which are similar for PBMC from non-allergic individuals and subjects with a high degree of allergy to the perennial house dust mite allergen and strong Th2 responses to Der p 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…In particular, the presence of IL-4 and/or IL-13-secreting Th cells [37]. Indeed, IL-13 production by HIstimulated PBMC from both atopics and non-atopics has been reported previously for P6 [38] and IL-4 production against other undefined antigens in HI extracts has also been reported [39]. It is noteworthy in this regard that IL-4 and IL-13 are highly pleiotrophic cytokines with multiple regulatory functions beyond IgE regulation, including an important role in modulation of macrophage activity.…”
Section: Discussionmentioning
confidence: 60%
“…In particular, the presence of IL-4 and/or IL-13-secreting Th cells [37]. Indeed, IL-13 production by HIstimulated PBMC from both atopics and non-atopics has been reported previously for P6 [38] and IL-4 production against other undefined antigens in HI extracts has also been reported [39]. It is noteworthy in this regard that IL-4 and IL-13 are highly pleiotrophic cytokines with multiple regulatory functions beyond IgE regulation, including an important role in modulation of macrophage activity.…”
Section: Discussionmentioning
confidence: 60%
“…The sustained Th2 response to colonising bacteria could downregulate Th1 and Th17 responses which could also have a role in the production of disease 22. The second is that the IgE antibody itself can enhance antigen capture via Fcε receptors on antigen-presenting cells and increase the recruitment of antibacterial T cells which, on balance, have been shown to be polarised to Th1,23 and these could alter the education of dendritic cells and hence signals to allergen-specific T cells 24. The inverse association of the IgE to Der p 1 and Der p 2 with the antibacterial IgE points to a downregulation of the anti-allergen Th2 response.…”
Section: Discussionmentioning
confidence: 99%
“…22 To assess the presence of T cells specific for NTHi within the CCR3 þ CD4 þ T-cell population, we determined the P6-specific proliferative response in purified peripheral blood CD4 þ T cells undepleted or depleted for CCR3 þ cells. To enable sufficient separation between the rare proliferating T cells and the nonresponding population, CFSE dilution in T cells was assessed after 6 days of stimulation.…”
Section: Ccl28 Receptor Expression On Nasal Mucosa-derived T Cellsmentioning
confidence: 99%
“…Analysis revealed that the subjects mounted a response to P6 following stimulation with antigen ( Figure 4a), as published by others. 17,22 Strikingly, when CD4 þ T cells were depleted for CCR3 þ cells with FACS sorting, the proliferative response was abrogated and not different from unstimulated control cells. Similar results were also obtained by depleting CD4 þ CCR3 þ cells with magnetic beads prior to antigen stimulation (data not shown), thus showing that the reduced proliferation was not an artifact introduced by cell passage through the FACS.…”
Section: Ccl28 Receptor Expression On Nasal Mucosa-derived T Cellsmentioning
confidence: 99%